Embryo and larvae development of Nilem Fish, Osteochilus vittatus reared in batik liquid waste - GISELA HARSIWI NUGRAHESTHI; GRATIANA EKANINGSIH WIJAYANTI; AULIDYA NURUL HABIBAH (Nusantara Bioscience, 2023)
Abstract. Nugrahesthi GH, Wijayanti GE, Habibah AN. 2023. Embryo and larvae development of Nilem Fish, Osteochilus vittatus reared in batik liquid waste. Nusantara Bioscience 15: 105-112. The embryonic and larval stages are critical phases of an organism's development. For aquatic organisms, development is affected by environmental factors such as liquid waste. A batik liquid waste is a waste product of the textile industry usually streamed directly into the aquatic environment. This study aimed to observe the effects of exposure to batik liquid waste effects on developing Nilem (Osteochilus vittatus Valenciennes, 1842) fish embryos and larvae. The research was conducted using a completely randomized design. One hundred two-celled embryos were kept in batik liquid waste with dilution concentrations of 0% (the control), 5%, 10%, 15%, and 20% of water until the age of 4 days after hatching with five replications. The time of embryo evaluation was 60th minutes, 120th minutes, and 180th minutes after fertilization; the larval stage evaluation time was the 24th, 48th, 72nd, and 96th hour after fertilization; five embryos were evaluated for each replication. The results showed that embryo exposure to batik liquid waste affected the height of the blastoderm embryo, accumulation of waste in the chorion of the embryo, deceleration of embryonic development, increased larval abnormalities, decreased the survival rate of larvae, and acceleration of yolk absorption of fish larvae. Embryos were successfully hatched and produced larvae only in the control and 5% batik liquid waste medium. Batik liquid waste interfered with O. vittatus embryo development and generated mortality above 5%.